2006
DOI: 10.1103/physrevstab.9.064402
|View full text |Cite
|
Sign up to set email alerts
|

Space charge modeling of dense electron beams with large energy spreads

Abstract: Theoretical and numerical studies of the transport in vacuum of multi-nC, multi-MeV electron beams are performed using several methods, including envelope models, a novel semianalytic approach using ellipsoidal shell decomposition, a modified electrostatic particle-in-cell method, and a point-to-point interaction model. The effects of space-charge forces on the longitudinal and transverse bunch properties are evaluated for various bunch lengths, energies, energy spreads, and charges. An evaluation of the vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 32 publications
(38 reference statements)
2
21
0
Order By: Relevance
“…We want to em-phasize here that studies of space-charge effects of such ultra-dense relativistic bunches can be simulated most accurately only with codes (such as GPT and CSRtrack [19]) which utilize point-to-point interactions (a result also found in Ref. [20]). In contrast, other codes merely based upon Poisson-solvers cannot cope with large relative particle motions within the bunch rest frame in case of large initial energy spreads and Coulomb explosioninduced motion.…”
Section: Space Charge Effectsmentioning
confidence: 99%
“…We want to em-phasize here that studies of space-charge effects of such ultra-dense relativistic bunches can be simulated most accurately only with codes (such as GPT and CSRtrack [19]) which utilize point-to-point interactions (a result also found in Ref. [20]). In contrast, other codes merely based upon Poisson-solvers cannot cope with large relative particle motions within the bunch rest frame in case of large initial energy spreads and Coulomb explosioninduced motion.…”
Section: Space Charge Effectsmentioning
confidence: 99%
“…The source size of the e beam [2 m (rms)] was extrapolated from both the e-beam size measured at the Compton interaction point [6 m (rms)] and its average divergence angle (10 mrad), assuming the space-charge blowup is negligible for our e-beam charge density and average energy [27]. Using the inferred source size, and the measured divergence angle of 5 mrad (for the 250-MeVcomponent of the e beam), we estimate a normalized rms e-beam emittance (" N ¼ e-source 250 MeV ) of 1 mm-mrad at 250 MeV.…”
Section: H Y S I C a L R E V I E W L E T T E R S Week Ending 12 Aprilmentioning
confidence: 99%
“…Although such a drastic modulation was observed from PIC simulations [195], no experimental evidence has been observed yet. Another possible explanation for smaller beam divergence with higher input intensity would be space charge effect of the injected electrons [109]. If space charge of the injected electron beam is stronger than the radial focusing force from the wakefield, Overall, the mean (maximum) output total energy U b was around 5 mJ (80 mJ), which was ∼ 0.3% (1.2%) of the input laser energy.…”
Section: × 10mentioning
confidence: 99%
“…Although it was demonstrated that a SM-LWFA could provide sufficient charge to perform chemical studies, a femtosecond pump probe experiment was not realized, probably due to the broadband property and space charge effect in high charge e-beams [109]. E-beams from SM-LWFA contained a total charge of nC, and such a high charge e-beam would be stretched out longitudinally during propagation in addition to the velocity difference between low and high energy electrons.…”
Section: Coulomb In a Very Short Time Duration ( Plasma Period ∼ 10 Fmentioning
confidence: 99%